An insertion variant of MGMT disrupts a STAT1 binding site and confers susceptibility to glioma - Huang, Liming; Xu, Wenshen; Yan, Danfang; Shi, Xi; You, Xin; Xu, Jiaqi; You, Pingping; Ke, Yuanyuan; Dai, Lian (Cancer cell international, 2021)
Background O 6 -methylguanine-DNA methyltransferase (MGMT) is a pivotal enzyme for repairing DNA alkylation damage. Epigenetic modification of MGMT has been well known as a promising prognostic biomarker for glioma. However, the significance of genetic variations of MGMT in glioma carcinogenesis has not been fully elucidated. Methods The associations between expression quantitative trait loci (eQTLs) of MGMT and glioma susceptibility were evaluated in a case–control study of 1056 individuals. The function of susceptibility locus for glioma was explored with a set of biochemical assays, including luciferase reporter gene, EMSA and supershift EMSA, ChIP, and siRNA knockdown. Results We found that rs11016798 TT genotype was associated with a significantly decreased risk of glioma (OR = 0.57, 95% CI 0.39–0.85; P = 0.006). Stratification analyses indicated that the association between rs11016798 and glioma was more pronounced in males (OR = 0.62, 95% CI 0.40–0.97; P = 0.035), older subjects (OR = 0.46, 95% CI 0.27–0.80; P = 0.006), WHO grade IV glioma (OR = 0.58, 95% CI 0.35–0.96; P = 0.033), and IDH wildtype glioma (OR = 0.43, 95% CI 0.21–0.88; P = 0.022). We characterized an insertion variant rs10659396 in the upstream of MGMT as a causative variant. The risk allele rs10659396 ins allele was demonstrated to downregulate MGMT expression by disrupting a STAT1 binding site. Knockdown of STAT1 remarkably attenuated MGMT expression. Moreover, the rs10659396 allele-specific positive correlation was observed between the expression of STAT1 and MGMT in population. Conclusions The study demonstrates that an insertion variant of MGMT rs10659396 confers susceptibility to glioma by downregulating MGMT expression through disrupting a STAT1 binding site. Graphic abstract